2017
DOI: 10.1007/s40820-017-0174-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Graphene/ITO Nanoparticle Hybrid Transparent Conducting Electrode

Abstract: The combination of graphene with conductive nanoparticles, forming graphene–nanoparticle hybrid materials, offers a number of excellent properties for advanced engineering applications. A novel and simple method was developed to deposit 10 wt% tin-doped indium tin oxide (ITO) nanoparticles on graphene. The method involved a combination of a solution-based environmentally friendly electroless deposition approach and subsequent vacuum annealing. A stable organic-free solution of ITO was prepared from economical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…al produced PLECs using silver-nanowires/single-walled-carbon-nanotubes bilayer as bottom electrode and silver-paste as top electrode [16]. These recent discoveries pushed the development of solution processed electrodes, mainly using hot materials, such as graphene, carbon-nanotubes and metallic nanostructures as active materials [15,[17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…al produced PLECs using silver-nanowires/single-walled-carbon-nanotubes bilayer as bottom electrode and silver-paste as top electrode [16]. These recent discoveries pushed the development of solution processed electrodes, mainly using hot materials, such as graphene, carbon-nanotubes and metallic nanostructures as active materials [15,[17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various methods have been devised for transferring graphene without a support layer, which are called “polymer-free” methods as described in Figure 3; for example, a thermal release tape-assisted transfer, using a tape with specific adhesives that strongly adheres to substrates at room temperature while losing adhesion at high temperature, and a metal-assisted transfer method, using a metal as a protective layer instead of a polymer [83,85]. In particular, the thermal release tape-assisted transfer method is likely to be suitable for large-scale production because it can inherit the roll-to-roll (R2R) production process for graphene growth [62,63]. For instance, Bae et al have successfully demonstrated the R2R production and coating of CVD graphene onto flexible substrate using a thermal release tape-assisted transfer method (Figure 2) [12].…”
Section: Fabrication Of Graphene-based Transparent Conducting Elecmentioning
confidence: 99%
“…Transparent conductive oxides, such as ITO and aluminum-doped zinc oxide (AZO), are widely used in electrodes, however the rigidity of these materials has limited their use as flexible electrodes. There have been attempts to improve the mechanical properties of ITO by fabricating a hybrid electrode using graphene and ITO [61,62]. Liu et al demonstrated that the graphene/ITO hybrid electrodes showed a resistance change (ΔR/R 0 ) of 17.78 after 20% tensile strain; meanwhile, the (non-hybrid) ITO electrode showed a resistance change of 125.91.…”
Section: Tces Of Graphene-related Materials Hybridized With Other mentioning
confidence: 99%
See 1 more Smart Citation
“…5,21-3 23 Importantly, doping can lead to changes in the conductivity, magnetism, transparency, and catalytic response. 6 Many of these systems have been studied at atomic resolution using transmission electron microscopy (TEM) 24,25 and electron energy loss spectroscopy (EELS). Annular dark field scanning transmission electron microscopy (ADF-STEM) can provide non-linear Z-dependent contrast that helps to discriminate the dopant from the C lattice with higher contrast than phase contrast TEM, however phase contrast TEM enables the dynamics to be observed at much faster time scales.…”
Section: Abstract: Adf-stem Gd Graphene 2d Materials Metallofullementioning
confidence: 99%